2017
DOI: 10.1002/mp.12342
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy evaluation of a six‐degree‐of‐freedom couch using cone beam CT and IsoCal phantom with an in‐house algorithm

Abstract: Errors of a new 6DoF couch were tested using CBCT images of a 3D phantom. The rotation errors were less than 0.3 degree and the translation errors were less than or equal to 0.8 mm in each direction. This level of accuracy is warranted for clinical radiotherapy utilization including stereotactic radiosurgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Theoretically, the 6-DoF couch united with kilovoltage cone beam computed tomography (kV-CBCT) can further reduce setup errors. This may lead to a potential situation that decreases the clinical target volume (CTV) to planning target volume (PTV) margins ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, the 6-DoF couch united with kilovoltage cone beam computed tomography (kV-CBCT) can further reduce setup errors. This may lead to a potential situation that decreases the clinical target volume (CTV) to planning target volume (PTV) margins ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is also a treatment machine, called tomotherapy, which can correct only three translational and one rotational axes . Zhang et al investigated the rotational accuracy of the 6DoF couch with cone‐beam CT, and they reported that the mean rotational errors ± SD for pitch, roll, and yaw angles were 0.028 ± 0.032°, −0.043 ± 0.058°, and −0.009 ± 0.033°, respectively. The rotational accuracy of our prototype device was measured using two different methods (the digital goniometer and cone‐beam CT), which is almost equivalent to the results reported by Zhang et al as shown in Result section 3.B.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al investigated the rotational accuracy of the 6DoF couch with cone‐beam CT, and they reported that the mean rotational errors ± SD for pitch, roll, and yaw angles were 0.028 ± 0.032°, −0.043 ± 0.058°, and −0.009 ± 0.033°, respectively. The rotational accuracy of our prototype device was measured using two different methods (the digital goniometer and cone‐beam CT), which is almost equivalent to the results reported by Zhang et al as shown in Result section 3.B. Moreover, the repeatability was less than the detection limit of the digital goniometer, as described in Result section 3.A.…”
Section: Discussionmentioning
confidence: 99%
“…The IsoCal phantom is a hollow cylinder with 16 tungsten-carbide ball bearings (BBs) arranged at a specified position. 15 While the purpose of this phantom is to calibrate between the isocenter and the image center, 16 it was used to determine the gantry angle in this study. The phantom images were acquired by the "triggered imaging" mode using the on-board kV imager at the source-detector distance (SDD) of 150 cm.…”
Section: A | Experimental Setupmentioning
confidence: 99%